KSHV viral load and Interleukin‐6 in HIV‐associated pediatric Kaposi sarcoma—Exploring the role of lytic activation in driving the unique clinical features seen in endemic regions. Issue 1 (31st October 2018) - El‐Mallawany, Nader Kim; Mehta, Parth S.; Kamiyango, William; Villiera, Jimmy; Peckham‐Gregory, Erin C.; Kampani, Coxcilly; Krysiak, Robert; Sanders, Marcia K.; Caro‐Vegas, Carolina; Eason, Anthony B.; Ahmed, Saeed; Schutze, Gordon E.; et al.
Abstract : Kaposi sarcoma (KS) is among the most common childhood malignancies in central, eastern, and southern Africa. Although its unique clinical features have been established, biological mechanisms related to the causative agent, KS‐associated herpes‐virus (KSHV), have yet to be explored in children. We performed a prospective observational pilot study to explore associations between KSHV viral load (VL), human interleukin‐6 (IL‐6) and IL‐10 levels, and clinical characteristics of 25 children with KS in Lilongwe, Malawi from June 2013–August 2015. The median age was 6.4 years. Lymphadenopathy was the most common site of KS involvement (64%), followed by skin and oral mucosa (44% each), woody edema (12%), and pulmonary (8%). Baseline samples for plasma KSHV VL, IL‐6 and IL‐10 analyses were available for 18/25 patients (72%) at time of KS diagnosis. KSHV VL was detectable at baseline in 12/18 (67%) patients, the median baseline IL‐6 level was 8.53 pg/mL (range 4.31–28.33), and the median baseline IL‐10 level was 19.53 pg/mL (range 6.91–419.69). Seven (39%) patients presented with an IL‐6 level > 10 pg/mL (exceeding twice the upper limit of normal). Detectable KSHV VL was significantly associated with lymphadenopathic KS ( p = 0.004), while having undetectable KSHV VL was associated with a higher likelihood of presenting with hyperpigmented skin lesions ( p = 0.01). Detectable KSHV VL and elevated IL‐6 levels are present in a subset of children with KS. Lytic activation of KSHV and associated elevation in KSHV VL may contribute to the unique clinical manifestations of pediatric KS in KSHV‐endemic regions of Africa. Abstract : What's new? Kaposi sarcoma is among the most common childhood malignancies in regions endemic for Kaposi sarcoma‐associated herpesvirus (KSHV), but virological characteristics of the disease remain undefined. Here the authors studied 25 children with Kaposi sarcoma in southeastern Africa and established links between distinct clinical patterns and elevated KSHV viral load and interleukin‐6 levels. The results points to a role of KSHV lytic activation and a potential KSHV inflammatory cytokine syndrome in the lymphadenopathic form of childhood Kaposi sarcoma.